A history of East European Jews - Haumann, Heiko, 1945- (Central European University Press, 2002)
Presents a history of East European Jewry from its beginnings to the period after the Holocaust. It gives an overview of the demographic, political, socio-economic, religious and cultural conditions of Jewish communities in Poland, Russia, Bohemia and Moravia. Interesting themes include the story of early settlers, the 'Golden Age', the influence of the Kabbalah and Hasidism. Vivid portraits of Jewish family life and religious customs make the book enjoyable to read.